Shiga-toxin producing Escherichia coli (STEC) and other enterobacteriaceae associated with ready-to-eat salad - Omoruyi, Iyekhoetin Matthew; Orieruo, Ufuoma Akpezi (International Journal of Biological Research, 2016)
Ready-to-eat (RTE) salads sold in Nigeria are poorly delineated sources of human exposure to pathogenic microorganisms. In this study, we investigated the current situation in Benin City, Edo state, Nigeria. Twenty-four samples of RTE salad were obtained from different open markets, and the presence of Shiga toxin-producing Escherichia coli (STEC) and other enterobacteriaceae were determined by established methods using both selective and chromogenic agars. All RTE salad samples were found to habour Escherichia coli while 16.7% were further confirmed for the presence of STEC. Other Enterobacteriaceae present included Klebsiella spp, Proteus spp, Enterobacter spp, Serratia spp and Salmonella spp. The antibiogramic profile revealed that all bacterial isolates obtained were resistant to augmentin and amoxicillin while only 11.1% were resistant to ciprofloxacin and ofloxacin. The percentage resistance for the Shiga-toxin producing strains of E. coli was 60% while Serratia showed resistance to all the antibiotics used. The results of this study showed that RTE salad sold in Benin City, Edo State, Nigeria could be a source of public health concern, and effort should be made to avert possible outbreak.
Keywords: Salad; Outbreak; Shiga Toxin-Producing E. coli; Enterobacteriaceae; Public Health.